PENGARUH MODEL GUIDED DISCOVERY LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMPN 22 PADANG - Asyinandani, Tasha Aura (Departemen Matematika, 2023)
The capability to communicate in the context of mathematics has an impact on mathematics learning outcomes. When students have effective communication skills, they can convey mathematical answers, concepts accurately and precisely. However, many students still lack proficient communication abilities in the mathematical context. One applicable model for enhancing students' abilities in communicating mathematical concepts is by utilizing the Guided Discovery Learning model. The aim of this study is to identify and evaluate whether students engaged in education through the Guided Discovery Learning model display better performance compared to those taught applying the direct instructional model in the eighth grade at SMPN 22 Padang. The research design used is a quasi-experiment employing a Non-equivalent posttest-only control group approach, conducted in the eighth-grade classrooms at SMPN 22 Padang. Sampling was conducted using a straightforward random sampling method, with Class VIII D chosen as the experimental group and Class VIII F as the control group. The instrument used is a final assessment of mathematical communication abilities Data analysis results indicated P-value = 0.002 ( .) This outcome suggests that the overall mathematical communication abilities of students were educated using the Guided Discovery Learning model surpassed those who were instructed through the direct teaching method.Keywords– Mathematical communication skill, Guided Discovery Learning, Direct Learning